Frustración magnífica y drama puro: el teatro de Legom - Vázquez Touriño, Daniel (Latin American Theatre Review, 2014)
The characters that populate the plays of Legom (Luis Enrique Gutiérrez Ortiz Monasterio) pertain to a family of literary beings who are unable to adapt to a dysfunctional society. This phenomenon links to the concept of the “pelado” featured in Cantinflas films and to the “utopia of the hunter” described by Zygmunt Bauman as a postmodern, hegemonic system that excludes and alienates. The tension between local and global is a fundamental aspect in the characters created by Legom. While the use of uniquely Mexican vulgarities establishes the “mexicanness” of his characters, their ideals and aspirations, albeit twisted and often misunderstood, are unmistakably transnational. Critics tend to use the term narraturgia to describe Legom’s dramatic production, yet closer analysis suggests that the playwright indeed strives to exclude the extra-dramatic in the creation and development of his characters.